[Em]powering communities? : explaining the changing role and nature of Costa Rica’s cooperatives from successful community-led rural electrification to failing community-led electricity generation - Ranalder,Lea (Master Thesis Series in Environmental Studies and Sustainability Science, 2017)
Concerns about energy-related emissions and energy dependence and security while also achieving the SDGs are fuelling the rising interest in socio-technical transitions towards more sustainable energy systems. Community energy projects have been proposed as a tool for this transition to renewable energy, but little is known about its potential to foster the wider transformation of the energy system. To comprehend the dynamics of system transformation, I use transition theory and conceptualize grassroots bottom-up groups as innovations in the electricity regime. Using Costa Rica as a case study, I study its community energy sector between the 1960s and today – as this is when its four cooperatives became active. This is a relevant case because Costa Rica is regarded as a success story for community energy: it has achieved almost universal electrification (with 99% of its electricity coming from renewables) with cooperatives playing a significant role in the electricity system. Considering this, I critically analyse the changing role and nature of Costa Rica’s cooperatives towards community-led transitions in both rural electrification and electricity generation, and towards what ends. My findings demonstrate that: (i) In the 1960s/70s the cooperative model of electrification emerged as grassroots community-led innovation within Costa Rica’s centralised electricity system. Cooperatives transformed not only the electricity distribution mode to realise rural electrification but subsequently also reconfigured the electricity generation system; cooperatives are nowadays part of the overall socio-technical electricity regime in Costa Rica; (ii) Contrary to the assumption that cooperatives are working towards communitarian electricity generation, cooperatives are part of a regime that is encapsulated in large-scale hydropower to remain in control of centralized electricity generation and in the process curtails decentralized small-scale renewables. These findings have two implications. Firstly, Costa Rica’s cooperatives have changed their nature and role in the electricity system - away from the communitarian discourse of energy community. Thus, they are failing to promote a transition to community-led electricity generation in Costa Rica. This changing nature also relates back to the question of how community energy should be defined. Secondly, considering the rising electricity demand coupled with social and environmental concerns about hydropower, I argue that community-led electricity generation could provide a holistic alternative. In the light of a highly centralised electricity regime, this would require transition management.
Keywords: community energy; transition pathway; rural electrification; renewable energy; hydropower; sustainability science